Genetic modulation of nephrocalcinosis in mouse models of ectopic mineralization: The Abcc6(tm1Jfk) and Enpp1(asj) mutant mice - Li, Qiaoli (2014)
Ectopic mineralization of renal tissues in nephrocalcinosis is a complex, multifactorial process. The purpose of this study was to examine the role of genetic modulation and the role of diet in nephrocalcinosis using two established mouse models of ectopic mineralization, Abcc6(tm1Jfk) and Enpp1(asj) mice, which serve as models for pseudoxanthoma elasticum and generalized arterial calcification of infancy, two heritable disorders, respectively. These mutant mice, when on standard rodent diet, develop nephrocalcinosis only at very late age. In contrast, when placed on an “acceleration diet” composed of increased phosphate and reduced magnesium content they showed extensive mineralization of the kidneys affecting primarily medullary tubules as well as arcuate and renal arteries, as examined by histopathology and quantitated by chemical assay for calcium. Mineralization could also be detected noninvasively by micro computed tomography. While the heterozygous mice did not develop nephrocalcinosis, compound heterozygous mice carrying both mutant alleles, Abcc6( tm1Jfk/+), Enpp1(+/asj), developed ectopic mineralization similar to that noted in homozygous mice for either gene, indicating that deletion of one Abcc6 allele along with Enpp1 haploinsufficiency resulted in renal mineralization. Thus, synergistic genetic defects in the complex mineralization/anti-mineralization network can profoundly modulate the degree of ectopic mineralization in nephrocalcinosis.